Evaluating a space for co-innovation: Practical application of nine principles for co-innovation in five innovation projects. (June 2017) - Coutts, Jeff; White, Toni; Blackett, Paula; Rijswijk, Kelly; Bewsell, Denise; Park, Nicola; Turner, James A; Botha, Neels
Primary Innovation is a 5-year collaborative initiative demonstrating and evaluating co-innovation, a systemic approach to innovation addressing complex problems, in five "innovation projects" (active case studies) in different agricultural industries. In defining the elements of co-innovation, Primary Innovation has emphasized nine principles that guide activity in the innovation projects. To understand how useful these principles were in guiding practice, and their influence on co-innovation, project participants assessed and reflected on how the principles were applied in practice, issues that arose, how each influenced the project, and how important each principle was perceived as being in influencing project outcomes. The nine principles should be understood in each individual project's context because their appropriateness and usefulness were affected by the type of problem being addressed and the stage of the project. It was also evident that they need to be built into the process from the outset.